Flipped learning by google apps in supporting learning and teaching during pandemic in Oman - Nurul Akhmal Mohd Zulkefli; Wardatul Akmam Din; Suyansah Swanto; Moosa Ahmed Ali Sulaiman (Global Academic Excellence, 2022)
The research study is commonly delivered using the traditional lecture format, followed by a question and answer session with students. Another approach is to divide students into groups, assign them themes to discuss, and then have them present the issues one by one. This learning technique, however, is not appropriate for use during a pandemic. In this study, students achieve the desired purpose of learning activities by utilizing the Active Learning approach and instructional strategy using Google Apps Learning Approach. Instructors can meet and talk with students both in-person and through the online system. This method is well-known as the Flipped Learning. This goal can be demonstrated by students arriving on time for individual discussion activities, explaining the topic, listening to other members' explanations, participating in conversations, exhibiting critical thinking, and leading physical or online discussion activities. However, because this activity takes place online, there are a number of challenges to overcome during the implementation phase, including internet network issues, data constraints, and device specs that do not allow learning activities—this study involved a total of five postgraduate students. This study was done from February to May 2022. The prior study used the questionnaire and got the expert's permission. The study was evaluated using descriptive quantitative statistics including standard deviation, percentage, frequency, and score. According to the report, students' average level of difficulty with Google Apps is 3.82.